Learn Rust in a month of lunches - MacLeod, David (Manning Publications, 2024)
Learn Rust in a Month of Lunches breaks down the Rust language into concise hands-on lessons designed to be completed in an hour or less. The examples are fun and easy to follow, so you'll quickly progress from zero Rust knowledge to handling async and writing your own macros. You won't even need to install Rust-the book's code samples run in the browser-based Rust Playground. There's no easier way to get started!
Includes index
Keywords: Rust (Computer program language); Computer programming; Rust (Langage de programmation); Programmation (Informatique); computer programming